The respiratory chain of Klebsiella aerogenes in urine-like conditions: critical roles of NDH-2 and bd-terminal oxidases - González-Montalvo, Martín A.; Sorescu, Jennifer M.; Baltes, Gabriella; Juárez, Oscar; Tuz, Karina (Frontiers in Microbiology, 2024)
Klebsiella aerogenes is an opportunistic nosocomial bacterial pathogen that commonly causes urinary tract infections. Over the past decades, K. aerogenes strains have acquired resistance to common antibiotics that has led to the rise of multidrug-resistant and even pandrugresistant strains. Infections produced by these strains are nearly impossible to treat, which makes K. aerogenes a global priority to develop new antibiotics and there is an urgent need to identify targets to treat infections against this pathogen. However, very little is known about the metabolism and metabolic adaptations of this bacterium in infection sites. In this work, we investigated the respiratory metabolism of K. aerogenes in conditions that resemble human urine, allowing us to identify novel targets for antibiotic development. Here we describe that, unlike other gram-negative pathogens, K. aerogenes utilizes the type-2 NADH dehydrogenase (NDH-2) as the main entry point for electrons in the respiratory chain in all growth conditions evaluated. Additionally, in urine-like media, the aerobic metabolism as a whole is upregulated, with significant increases in succinate and lactate dehydrogenase activity. Moreover, our data show that the bd-I type oxidoreductases are the main terminal oxidases of this microorganism. Our findings support an initial identification of NDH-2 and bd-I oxidase as attractive targets for the development of new drugs against K. aerogenes as they are not found in human hosts.